Neurological adverse events associated with antidepressants: a comprehensive 22-year analysis of the FDA adverse event reporting system - Yu, Qian; Yao, Jingyang; Li, Enping; Xia, Mingkai; Hu, Ziang; Xiao, Yun; Huang, Jianliang; Lei, Mingsheng (Frontiers in Pharmacology, 2025)
IntroductionAntidepressants are among the most commonly prescribed medications worldwide; however, comprehensive analyses of neuropsychiatric adverse events (AEs) across different drug classes and patient subgroups remain scarce.MethodsThe primary objective of this study was to utilize the U.S. Food and Drug Administration’s Adverse Event Reporting System (FAERS) database to identify and characterize neurosafety signals associated with seven classes of antidepressants. Individual case safety reports involving 33 antidepressants were analyzed from 2004 to 2025, focusing on neurological AEs. The reports’ odds ratios (RORs) were calculated and presented. Kaplan-Meier methods were employed for time‐to‐event analysis, and subgroup analyses were conducted to explore patterns specific to age, gender, and drug class. ResultsThe database contained 127,568 neurological AEs, accounting for 33.8% of the total reports of antidepressant. Reported data were traced to 98 countries and regions, primarily from North America and Western Europe. The number, type, and severity of reported neurological AEs varied significantly by gender, age groups, and drug categories. In the adverse reaction signal analysis, a series of strong adverse reaction signals were identified, with “neonatal movement disorders” showing the strongest signal (ROR = 51.97), and serotonin syndrome signals were also prominent. Distinct signals were also identified in the analysis of various drug categories. For instance, SSRIs and SNRIs exhibited signal patterns associated with neonatal adaptation, NaSSAs displayed the strongest single signal in “motor dysarthria,” and MAOIs were associated with severe motor emergencies. NDRIs demonstrated excessive activation of the sympathetic nervous system, while the strongest signals for SARI/SMS drugs were concentrated in “visual stereotypy” and “hypoglycemic encephalopathy.” TCAs exhibited the broadest spectrum of neurological AEs. Serotonin syndrome is present in nearly every drug group. The median onset time for neurological AEs was 45 days. Significant differences were observed between drug categories, with MAOIs having the longest median onset time (91 days). Onset time was unrelated to gender but closely associated with age groups. ConclusionOverall, this 22‐year database analysis revealed diverse patterns of neurological AEs associated with antidepressants, providing evidence to inform safe clinical decision‐making regarding drug use across populations.